Implementation of an online emergency education programme at a public university in Mexico - González Barranco, Patricia; Balderas Rentería, Isaías; Esquivel Ferriño, Patricia Cristina; Gracia Vásquez, Yolanda Araceli (Publishing Services, 2020)
The Universidad Autónoma de Nuevo León (UANL) is a public university situated in Monterrey, Mexico. It has more than 206,000 students in high school and higher education and 1,157 students registered in the Químico Farmacéutico Biólogo/Chemist Pharmacist Biologist programme. Most of the educational programmes are in person, only a few continual education courses were given remotely, for which UANL used a platform called Nexus, for all media and educational resources. This platform is also used for University students to submit and evaluate homework for the in-person classes. Only approximately 10% of the University’s staff had previously delivered lectures online, despite all of them having, as students, attended online continuous education programmes. On 17th March 2020, UANL decided to stop all in-person activities for students as recommended by the government and one week later this was extended to include faculty and administrative staff. The regular termly calendar was scheduled from 20th January to 19th June 2020, a 20-week term. The term was in its ninth week when the pandemic interrupted the learning schedule.